2022
DOI: 10.3390/metabo12060568
|View full text |Cite
|
Sign up to set email alerts
|

FADS Polymorphisms Affect the Clinical and Biochemical Phenotypes of Metabolic Syndrome

Abstract: Long-chain polyunsaturated fatty acids (LC-PUFAs) play important roles in human health, from controlling inflammation to lipid and glucose homeostasis. In our previous study, which employed a cluster analysis of a plasma fatty acid (FA) pattern, we identified two clusters of metabolic syndrome (MetS) independent of clinical and biochemical parameters within the whole study group (controls together with metabolic syndrome (MetS) patients). FA desaturase (FADS) genes are the key regulators of LC-PUFA metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 88 publications
0
2
0
Order By: Relevance
“…Since genetic variants affect lipid metabolism which is closely associated with MetS ( 33 ), attention focused on the association between MetS and genetic factors ( 34–36 ), and FADS genotype has been found to contribute to biochemical and metabolic variations in the MetS. In our pilot study in a routine clinical setting, we chose the FADS1 SNP rs174546 which has been reported to be in linkage disequilibrium (LD) with other FADS1 variants as a representative variant for differences in the FADS1 genotype ( 12 , 36 ) and confirmed this with the SNPs rs174547 and rs174550.…”
Section: Discussionmentioning
confidence: 99%
“…Since genetic variants affect lipid metabolism which is closely associated with MetS ( 33 ), attention focused on the association between MetS and genetic factors ( 34–36 ), and FADS genotype has been found to contribute to biochemical and metabolic variations in the MetS. In our pilot study in a routine clinical setting, we chose the FADS1 SNP rs174546 which has been reported to be in linkage disequilibrium (LD) with other FADS1 variants as a representative variant for differences in the FADS1 genotype ( 12 , 36 ) and confirmed this with the SNPs rs174547 and rs174550.…”
Section: Discussionmentioning
confidence: 99%
“…While EPA and DHA can be synthesized from alpha-linolenic acid (ALA) in humans, most studies suggest that the conversion of ALA to EPA is less than 5% and the conversion to DHA is less than 0.05% (3). N-3 FA blood levels, metabolism and uptake from bloodstream can be affected by individual conditions and genetic determinants (4,5).…”
Section: Introductionmentioning
confidence: 99%